ANALISIS STATUS KEBERLANJUTAN KAKAO (Theobroma cacao L) DI KABUPATEN BANTAENG - Anwar Anwar; Muliati Galib; Farizah Dhaifina Amran (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2022)
Cocoa cultivation business that still has great potential in the future. The problem faced by farmers in cocoa cultivation is that farmers are still lacking in implementing post-harvest management that can provide added value and competitiveness of cocoa quality in the market. This study aimed to 1) analyze the status of cocoa sustainability in Gantarangkeke sub-regency, Bantaeng Regency; 2) analysing the sensitive leverage to the sustainability of cocoa in the Gantarangkeke sub-district. Based on the results of the analysis of the social and cultural dimension index value of 55.19 percent and infrastructure and technology of 51.66 with the category of quite sustainable. While the ecological dimension is 46.68 percent, economy 36.69 percent and legal and institutional 27.45 percent with the category of less sustainable. The results of the analysis of leverage factor, there are fourteen sensitive attributes that affect the sustainability of cocoa in Gantarangkeke sub-district, Bantaeng district. Improvement of attributes, especially sensitive attributes, can improve the cocoa sustainability index.